Confucian Tradition and Global Education - De Bary, Wm. Theodore, 1919-2017 (Book collections on Project MUSE., 2007)
"Drawn from a series of lectures that Wm. Theodore de Bary delivered in honor of the Chinese philosopher Tang Junyi, Confucian Tradition is a unique synthesis of essay and debate concerning the future of Chinese education and the potential political uses of Confucianism in the contemporary world."--Jacket